EFL Students' Perceptions towards Lecturer's Corrective Feedback in Speaking Class - Wardani, Happy Kusuma; Nisa, Lisma Elizatun; Maciąg, Alina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This article aims to investigate the EFL students’ perceptions and preferences towards the lecturer’s corrective feedback in a speaking class. The method used was descriptive qualitative research design. Twenty-four students from the first semester of English Language Education Program in a private university in Gresik were purposively selected as the participants of this research. They were invited to fill in the questionnaire and participate in the interview session. The findings showed the students’ positive point of view towards the lecturer’s corrective feedback during speaking class. More than 50% students stated that lecturer’s corrective feedback was necessary as the self-reflection to build their self-confidences and to enrich their knowledge in the speaking skill. Most students admitted that lecturer’s corrective feedback brought positive impacts to their speaking performances.